Examining Training Performance of TVET Trainers With/Without TVET Certificate in the Republic of Korea - Woo, Heajung; Kim, Woocheol; Yi, Yejih; Yoon, & Gwansik (Journal of Technical Education and Training, 2018)
TTVET trainer plays an important role in ensuring the quality of TVET.  TVET Trainer certificate can function as a signal to show the level of their teaching and learning competency. However, only some trainers have TVET trainer certificate. The importance of the role of TVET trainer certificate has recently been emphasized in the Republic of Korea. This study aimed to investigate the effects of the TVET trainers with/without certificate on the training performance. Independent t-tests were conducted to examine the impacts of the trainers on the training performance such as academic achievement, satisfaction level, employment rate and completion rate of trainees. The results showed that TVET trainers with certificate (TWC) tended to be higher in satisfaction level, employment rate, completion rate and academic achievement than TWOCs. On the other hand, the completion rate of trainees learned from TWCs was lower than the result of TWOCs. Based on the results, suggestions for the quality improvement of TVET trainers are discussed.